Penerapan Metode Kopra dalam Rekomendasi Pemilihan Tempat Usaha Kuliner di Kota Semarang - Darmaji, Satrio Wisnu; Budiarso, Zuly (LPPM UNIKA Santo Thomas Medan, 2022)
Culinary businesses such as cafes, restaurants or rice stalls need a place that is sufficient for selling activities. The growing number of new traders makes the competition between traders more and more. This also affects the availability of space. The city of Semarang is a city that has a lot of food vendors. The rapid growth of food businesses that occurred in the city of Semarang in 2020 made less and less available places to sell. Other factors such as rental costs, facilities that will be obtained and various other factors also affect the choice of a culinary business in the city of Semarang. That way, the consideration of choosing a place will be more and more. This study aims to create a recommendation system for choosing a culinary business place in the city of Semarang using the Complex Proportional Assessment (COPRAS) method. The assessment criteria for the COPRAS method in the selection of a culinary business place in the city of Semarang consist of the criteria for rental fees with a weight of 0.4, area of a place with a weight of 0.3, facilities with a weight of 0.2 and parking area with a weight of 0.1. The recommendation results from the selection of criteria for rental fees between Rp. 500.000-Rp. 1.500.000 are Warung Qampung with a value of Ui = 1.000. Warung Qampung has the highest value because it has the cheapest rental costs where the criteria for renting costs have the highest percentage weight.